Implementation of Passing Drills to Improve Chest Passing Skills Of Sunday Morning Basketball Club Athletes in Lubuklinggau City - Mardhatillah, Dahtriansyah; Syafutra, Wawan; Febrianti, Yuli (STKIP Paasundan Press, 2025)
The purpose of this study was to determine whether the accuracy of chest pass performance among athletes of the Sunday Morning Basketball Club in Lubuklinggau City improves after the implementation of passing drills. This research used an experimental method with a one-group pretest-posttest design. The population consisted of 20 athletes from the Sunday Morning Basketball Club, and the sampling technique used was total sampling (saturated sampling). Data analysis was conducted using the paired sample t-test. Based on the results of the paired samples test, the mean of the paired differences was 2.800, indicating the average improvement in chest pass scores from the pretest (5.00) to the posttest (7.80). The confidence interval for the difference ranged from 2.381 to 3.218 (95% CI). The t-value obtained was 14.000 with a significance level (p-value) of 0.000. Since the significance value (2-tailed) was 0.000 < 0.05, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This indicates that there is a significant effect of passing drills using modified weighted basketballs on improving the chest pass accuracy of athletes at the Sunday Morning Basketball Club in Lubuklinggau City.